Ubiquitous computing applied to mental health: trends and research focus - Büttenbender, Paulo C.; Barbosa, Jorge L.V.; Martins, Márcio G. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
The burden of neuropsychiatric disorders is increasing and there is a considerable problem in being able to deliver quality treatment to all affected population. The advance of mobile and ubiquitous computing in the last decade can open new ways of monitoring and treating neuropsychiatric disorders. The aim of the review was to systematically search the literature for studies applying ubiquitous computing and understand which disorders are being researched. A systematic mapping was conducted in ACM, IEEE, PubMed and PsychINFO including papers up to March 2018. 1425 papers were found during academic database search, of which 213 were selected for analysis given the predefined selection criteria. Preliminary results for one question show that the research of ubiquitous and mobile computing applied to mental healthcare is clearly growing over the past decade, with majority of the works focused on Depression, Bipolar, Schizophrenia, Mood disorders and PTSD.